Influence of Surface Roughness on the Cavitation Wear of P265GH and X2CrNi18-9 Steel Cavitation Generators - Tomasz Linek; Tomasz Tanski; Wojciech Borek (Communications - Scientific letters of the University of Zilina, 2018)
The aim of this paper was to determine the effect of surface roughness of cavitation generators made from two different materials: P265GH steel, with a ferritic-pearlitic structure, and X2CrNi18-9 (304L) steel with an austenitic structure on the mass loss and cavitation wear. Cavitation generators were tested in the conditions of cavitation wear environment continuously for 500 PMHs in a specially designed and constructed author's stream and flow device. Based on the carried out experiments was confirmed that the highest mass loss - 0.1752 g is seen for a sample of P265GH steel wet sanded with paper with the grain size of 1000. The smallest mass loss was recorded for the cavitation generator made of X2CrNi18-9 (304L) steel, sanded with sandpaper with the grain size of 2500. Certainly, the smallest number of cavitation wear effects was found for a cavitation generator made of austenitic steel X2CrNi18-9 (304L). Few places were identified based on macroscopic photographs, especially near the edges of the straight-through openings, but their number was much smaller than for the ferritic-pearlitic steel, which is associated most of all with the properties of austenitic chromium - nickel steel.